Implementasi Pendidikan Kewirausahaan Melalui Inovasi Terhadap Usaha Mahasiswa Universitas Teknologi Sulawesi Utara - Diana Wangania; Lady Giroth; Hendry Rumengan; Frangky Robial; Mei Hastuti; Salsabila Putri; Theresa Mamahit; Aprilia Hanse; Dwikky Putra; Yoberts Taroreh (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to increase student engagement in entrepreneurial activities, with a focus on marketing and product sales strategies. The results showed that students’ interest in entrepreneurship is high, and marketing and sales skills are the main reference in implementing their business ideas. Thus, this study developed and tested practical training strategies, including product sales simulations, group work, and mentoring by business practitioners on campus. The implementation of these strategies significantly improved students’ marketing and sales skills. The results of this entrepreneurial practice provided students with valuable insights into the key success factors in entrepreneurship. The findings contribute to the practical and academic understanding of efforts to increase student engagement in entrepreneurship, particularly through the development of product marketing and sales skills, with implications that can help individual students when they want to be entrepreneurial.